Polymer Flow Influenced by Mold Cavity Surface Roughness - Stanek, Michal; Manas, Miroslav; Ovsik, Martin; Reznicek, Martin; Senkerik, Vojtech; Janostik, Vaclav (Manufacturing Technology Journal, 2019)
Polymer injection molding is the most used technology of polymer processing nowadays. It enables the manufacture of final products, which do not require any further operations. Working of shaping cavities is the major problem involving not only the cavity of the mold itself, giving the shape and dimensions of the future product, but also the flow pathway (runners) leading the polymer melt to the separate cavities. This paper shows the influence of cavity surface roughness, polymer material (with different flow properties) and technological parameters on the flow length of polymers into mold cavity. Application of the measured results may have significant influence on the production of shaping parts of the injection molds especially in changing the so far used processes and substituting them by less less expensive production processes which might increase the competitiveness of the tool producers and shorten the time between product plan and its implementation.
Keywords: Injection Molding; Surface Roughness; Polymer; Fluidity; Tools